2022
DOI: 10.1016/j.jcot.2022.101784
|View full text |Cite
|
Sign up to set email alerts
|

REAL-TIME strain elastography: Applications in musculoskeletal system

Abstract: Background: Strain or compression sonoelastography (CE) provides a colour-coded elastogram representing tissue elasticity by measuring tissue deformability after repeated probe compression. Elastographic ultrasound (EUS) is a valuable tool for screening diagnosis and follow-up of inflammatory, degenerative, benign and malignant neoplastic pathologies of skin, subcutaneous tissue, muscles, tendons, ligaments, fascia and nerves; help in targeted biopsy; monitor healing tendons after surgery or nerve stiffness ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Similar greater sensitivity of sonoelastography versus grayscale US for early stages of tendinopathy have been reported in the Achilles, quadriceps, biceps, supraspinatus, and other tendons 9,14–17 . Sonoelastography has also been applied to osteoarthritic cartilage, the transverse ligament in carpal tunnel syndrome, myopathies, ligaments, rheumatoid synovitis, methotrexate hepatotoxicity (important in rheumatology), meniscal disease, trigger finger, and musculoskeletal tumors with similar changes in elasticity of the relevant tissue with variable sensitivity and specificity for pathology versus alternative imaging methods 14–25 …”
mentioning
confidence: 86%
See 3 more Smart Citations
“…Similar greater sensitivity of sonoelastography versus grayscale US for early stages of tendinopathy have been reported in the Achilles, quadriceps, biceps, supraspinatus, and other tendons 9,14–17 . Sonoelastography has also been applied to osteoarthritic cartilage, the transverse ligament in carpal tunnel syndrome, myopathies, ligaments, rheumatoid synovitis, methotrexate hepatotoxicity (important in rheumatology), meniscal disease, trigger finger, and musculoskeletal tumors with similar changes in elasticity of the relevant tissue with variable sensitivity and specificity for pathology versus alternative imaging methods 14–25 …”
mentioning
confidence: 86%
“…The low cost, convenience, noninvasive nature, lack of ionizing radiation, direct relevance to palpable anatomy, point‐of‐care applicability, and increasing number of applications indicate that US will only increase in use in musculoskeletal medicine 1–4 . Sonoelastography is another powerful method available to observe the musculoskeletal system, and appears particularly valuable in detecting early tendinopathies, areas of myopathy suitable for biopsy, pursuing complaints of localized musculoskeletal pain, analyzing soft tissue masses, and research applications in musculoskeletal medicine 14–25 . Shear wave elastography in particular permits rapid quantitative assessments of musculoskeletal structures and will be particularly valuable at the beside, in research studies and clinical trials, and in monitoring disease presence, progression, and response to therapy, especially in muscle and tendon disease.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous clinical SEL applications and studies were found to evaluate diagnosis and assessment of changes in tissue stiffness and elasticity in pathological conditions. [9][10][11][12][13][14] However, clinical utility of elastography has been infrequently studied in LE and has not been evaluated with tendon thickness.…”
Section: The Ultrasound Elastography Findings In Lateral Epicondyliti...mentioning
confidence: 99%